Evidence that facilitative glucose transporters may fold as beta-barrels. - Fischbarg, J (1993)
A widely accepted model for the structure of the facilitative glucose transporters (GLUTs) predicts that they form 12 transmembrane alpha-helices and that the highly conserved sequence Ile-386-Ala-405 in GLUT1 is intracellular. We raised a polyclonal antibody against a synthetic peptide encompassing this conserved sequence and found that antibody treatment increased 2-deoxy-D-glucose (DOG) uptake in Xe-nopus oocytes expressing GLUT1, GLUT2, or GLUT4 only when applied to the extracellular side. This effect was dose dependent and was specifically blocked by competition with the peptide Ile-386-Ala-405; it was due to a decrease in the Km for the transport of DOG. To ascertain GLUT orientation, we raised anti-peptide antibodies against the last 21 and 25 C-terminal amino acids of GLUT1 and GLUT4, respectively, which were previously shown to be intracellular. These antibodies increased DOG uptake when injected into oocytes expressing GLUT1 and GLUT4, but not when added extracellularly. Prompted by the noted discrepancy, we found sequence similarity between GLUTs and porins, two of which are known from crystallography to form 16-stranded transmembrane antiparallel beta-barrels. Analysis of the hydrophobicity, amphiphilicity, and turn propensity of GLUT1 leads us to propose that GLUTs fold as porin-like transmembrane beta-barrels. This model is consistent with the results of the present antibody studies and also with previously published experimental evidence inconsistent with the 12-helix model.